How Numerical Unbalance Constraints Physical and Tactical Individual Demands of Ball Possession Small-Sided Soccer Games - Nunes, Nuno André; Gonçalves, Bruno; Coutinho, Diogo; Travassos, Bruno (Frontiers in Psychology, 2020)
This study aimed to explore the effects of playing different unbalanced ball possession small-sided games on external workload (distance cover while walking, running and sprinting, and max speed), individual tactical actions (number of passes with dominant and non-dominant foot) and internal load (rating of perceived exertion, RPE) in under-23 soccer players. Participants played 4v2, 4v3, 4v4, 4v5 and 4v6 SSGs on a 30x25m playing area. Data were analysed under opponent-based perspective, by fixing one team (4vX), and by cooperation-based perspective according to teammates (4v2+X). GPS monitors were used to collect and compute external workloads and individual tactical actions, and Borg Scale CR10 to evaluate RPE. High-Superiority (4v2), Superiority (4v3) and Very Low-Cooperation (4v2+0) formats allow players in balanced teams to cover more distance while walking; on the other side, Inferiority (4v5), High-Inferiority (4v6) and Very High-Cooperation (4v2+4) make players to sprint more and practice more individual tactical actions as a resultant emergent behavior; all players in SSGs conditions of lower number conditions perceived the exercise more intense, especially in situations of less two players. Overall, playing in high inferiority situations (4v2 and 4v6) may be used to increase physical demand for the outnumbered team, while coaches may use low superiority situations to adjust the task complexity when developing the players’ individual tactical actions.